Pengaruh Motivasi Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Melalui Kompensasi Sebagai Variabel Intervening Pada PT RPSM Kinali Pasaman Barat - ., Metrawati; Candana, Dori Mitra; Afuan, M. (CV. ITTC INDONESIA, 2026)
This research tres primary data obtained by distributing questionaires to 60 employees as respondents at PT RPSM (Rimbo Panjang Sumber Makmur), Kinali Passaman Barat. The analiytical method used in this study is Structural Equation Modeling (SEM) version 3 with the Partial Least Square (PLS) approach. The results of this study indicated that (1) work motivation has a positive and significant effect on compensation. (2) job satisfication has a positive and significant effect on compesation. (3) work motivation has a negative and insignificant effect on employee perfomance. (4) job satisfication has a positive and significant effect on employee perfomance. (5) compensation has a positive and significant effec on employee perfomance. (6) compensation is not able to mediated the effect of work motivation on employee perfomance. (7) compensation is able to mediated the effect of job satisfication on employee perfomance.